2017
DOI: 10.1039/c6ra27345a
|View full text |Cite
|
Sign up to set email alerts
|

Development of functionalized abamectin poly(lactic acid) nanoparticles with regulatable adhesion to enhance foliar retention

Abstract: Functionalized abamectin poly(lactic acid) nanoparticles with different adhesion abilities to crop foliage can regulate folia retention of abamectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(101 citation statements)
references
References 31 publications
3
98
0
Order By: Relevance
“…Polyphenols have exhibited good resistance to UV radiation and to photothermal effects [46], and, for these reasons, are typically used as sunscreens in various cosmetics. Prior work has also demonstrated that the encapsulation of Av is an effective way to improve photostability [15,47]. In the present work, the formation of TA/Fe 3+ films on the Av particles was predicted to partly shield these granules from UV light, and this is confirmed by the photodegradation results presented in Figure 4.…”
Section: The Photodegradation Of Avermectin Wdg Formulationssupporting
confidence: 74%
See 3 more Smart Citations
“…Polyphenols have exhibited good resistance to UV radiation and to photothermal effects [46], and, for these reasons, are typically used as sunscreens in various cosmetics. Prior work has also demonstrated that the encapsulation of Av is an effective way to improve photostability [15,47]. In the present work, the formation of TA/Fe 3+ films on the Av particles was predicted to partly shield these granules from UV light, and this is confirmed by the photodegradation results presented in Figure 4.…”
Section: The Photodegradation Of Avermectin Wdg Formulationssupporting
confidence: 74%
“…In detail, firstly, the lettuce foliage was cut into 8 mm diameter circles, secondly, the circles were put into different concentration solutions for 10 s; after drying the circles under the room temperature, finally, the target species were put onto the leaf. After 3 days, the activity of the creature was observed [15].…”
Section: Biological Activity Tests Of Avermectin and Azoxystrobin Formentioning
confidence: 99%
See 2 more Smart Citations
“…When stored at 0 • C and 25 • C, the MPS and PDI of the nanocapsule suspensions remained relatively stable, implying that the dual-functionalized pesticide nanocapsules had the desired physical stability. However, storage at 54 • C accelerated the process of the dual-functionalized pesticide nanocapsules approaching the glass transition temperature of PLA, which caused PLA to change from a rigid state to a flexible state [54,55], resulting in a reduction in particle size. However, the pesticide samples are not expected to experience such high temperatures under normal circumstances, so the prepared nanocapsules are still regarded as having good storage stability.…”
Section: Foliar Spread and Contact Angle Evaluation Of Dual-functionamentioning
confidence: 99%